The Effect of Ease of Use, Information Quality, and Service Quality on Purchase Decisions at Shopee Marketplace - Arista Prima Dini; Yunita Anggarini; S. M. Yasmin (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the influence of ease of use, information quality, and service quality on purchasing decisions at Shopee marketplace. This research is a quantitative one using non-probability sampling method completed by a purposive sampling technique. The number of samples used in this research are 100 respondents aged of over 18 years old and live in the Special Region of Yogyakarta and had made a purchase transaction at Shopee marketplace. The analytical method used is logistic regression analysis. The results of the study show that ease of use and service quality have positive and significant effects on purchasing decisions at Shopee marketplace, while information quality has no effect on purchasing decisions on the Shopee marketplace.